PKM permainan tradisional Desa Taeng Kabupaten Gowa - Kasman Kasman; Andi Atssam Mappanyukki (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
Changes not only occur in the social environment but also on the children's play pattern. The process and way of playing children from the day experienced developments. Nowadays, children rarely know traditional games, even those who do not know traditional games. Change is the movement of the structure in question according to the time change. Indonesian children should actually be able to maintain this traditional game. Traditional games are not merely games, in which there are cultural elements that are strongly inherent and must continue to be preserved. The method used in this activity is Model Technical Assistance in the form of Training and Workshop which is carried out by providing training and providing models in the form of workshops to children and parents about traditional games. The advice given with this activity, if parents more emphasize the traditional game in the appeal with games that are game on line. Local government in this case education Office of District and City can conduct regular training in both schools and villages.